Homogenization and materials design of mechanical properties of textured materials based on zeroth-, first- and second-order bounds of linear behavior - Lobos Fernández, Mauricio (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2018)
This work approaches the fields of homogenization and of materials design for the linear and nonlinear mechanical properties with prescribed properties-profile. The set of achievable properties is bounded by the zeroth-order bounds (which are material specific), the first-order bounds (containing volume fractions of the phases) and the second-order Hashin-Shtrikman bounds with eigenfields in terms of tensorial texture coefficients for arbitrarily anisotropic textured materials.